Framework for R&D&I activities in the steel industry in popularizing the idea of industry 4.0 - Bożena Gajdzik; Radosław Wolniak (Journal of Open Innovation: Technology, Market, and Complexity, 2022)
The research and development activity of a company determines the innovativeness of enterprises and economies. This kind of activity simultaneously influences the pace of their development and the level of competitiveness. With this in mind, the article-against the background of the characteristics of research and development activities - defines a framework for R&D&I activities for the steel industry in the conditions of popularization of the concept of Industry 4.0 and analyzes expenditures on R&D&I activities in Poland in 2010-2019. This topic is important because steel is one of the most important materials for the construction and the manufacture of steel products. It is very important to adjust the steel industry to the new market condition using research and development activities. The analysis was performed on the basis of data on expenditures on R&D&I activities by internal expenditures on R&D, expenditures on product and business process innovations and outlays on fixed assets for environmental protection through investments. The target of the paper is to find response on the three research questions formulated in the paper: what is the dynamics of the changes in the R&D expenditures in the Polish steel industry in 2010-2019 in comparison with the total industry in the country; what is the dynamics of changes in investment expenditures on new products and business process innovations in the Polish steel industry in 2010-2019; what is the level (dynamics) of investment outlays in environmental innovations in the Polish steel industry in 2010-2019? To conduct this analysis, we used the following methods: critical literature analysis, secondary data analysis, statistical methods. Industry 4.0 implementation in the steel industry has a strong, positive influence on the innovativeness of the company and on spending on innovations. On the basis of the data analyzed in the paper we observed that the increase of expenditure on R&D in the Polish steel industry was similar to that of other industries. As a result of the research, it was found that the dynamics of R&D expenditure in the Polish steel industry was consistent with the dynamics of expenditure calculated for the entire Polish Industry. At the same time, the sharp increase in R&D expenditure since 2018 was related to the implementation of the Industry 4.0 concept in the Polish industry. An interesting result of our research is the observed time lag in the form of a postponement of the growth of R&D expenditure after the emergence of the Industry 4.0 concept. We also observed that environmentally fixed capital expenditures may show fluctuating dynamics due to business cycles and legal restrictions to protect the environment. The added value of the publication is the framework of R&D&I activities for the steel industry and an in-depth analysis of R&D&I expenditures on the example of the metal producers in Poland in the last decade of growing interest in the concept of Industry 4.0 (I 4.0).
Keywords: 650; innovativeness; open innovation; business process; Industry 4.0 (I 4.0); sustainable production